Multisystem screening reveals SARS‐CoV‐2 in neurons of the myenteric plexus and in megakaryocytes. Issue 2 (31st March 2022) - Gray‐Rodriguez, Sandra; Jensen, Melanie P; Otero‐Jimenez, Maria; Hanley, Brian; Swann, Olivia C; Ward, Patrick A; Salguero, Francisco J; Querido, Nadira; Farkas, Ildiko; Velentza‐Almpani, Elisavet; Weir, Justin; Barclay, Wendy S; et al.
Abstract: SARS‐CoV‐2, the causative agent of COVID‐19, typically manifests as a respiratory illness, although extrapulmonary involvement, such as in the gastrointestinal tract and nervous system, as well as frequent thrombotic events, are increasingly recognised. How this maps onto SARS‐CoV‐2 organ tropism at the histological level, however, remains unclear. Here, we perform a comprehensive validation of a monoclonal antibody against the SARS‐CoV‐2 nucleocapsid protein (NP) followed by systematic multisystem organ immunohistochemistry analysis of the viral cellular tropism in tissue from 36 patients, 16 postmortem cases and 16 biopsies with polymerase chain reaction (PCR)‐confirmed SARS‐CoV‐2 status from the peaks of the pandemic in 2020 and four pre‐COVID postmortem controls. SARS‐CoV‐2 anti‐NP staining in the postmortem cases revealed broad multiorgan involvement of the respiratory, digestive, haematopoietic, genitourinary and nervous systems, with a typical pattern of staining characterised by punctate paranuclear and apical cytoplasmic labelling. The average time from symptom onset to time of death was shorter in positively versus negatively stained postmortem cases (mean = 10.3 days versus mean = 20.3 days, p = 0.0416, with no cases showing definitive staining if the interval exceeded 15 days). One striking finding was the widespread presence of SARS‐CoV‐2 NP in neurons of the myenteric plexus, a site of high ACE2 expression, the entry receptor for SARS‐CoV‐2, and one of the earliest affected cells in Parkinson's disease. In the bone marrow, we observed viral SARS‐CoV‐2 NP within megakaryocytes, key cells in platelet production and thrombus formation. In 15 tracheal biopsies performed in patients requiring ventilation, there was a near complete concordance between immunohistochemistry and PCR swab results. Going forward, our findings have relevance to correlating clinical symptoms with the organ tropism of SARS‐CoV‐2 in contemporary cases as well as providing insights into potential long‐term complications of COVID‐19. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.